THE SOLUTION OF HUMAN CAPITAL PROBLEMS IN CENTRAL ASIA IN NEW UZBEKISTAN (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The concept of human development dates back to ancient times. Since the era of Greek scholars such as Plato, Socrates, and Aristotle, attention has been paid to the factor of human progress. During Aristotle’s time, the lifestyle of people living in city-states (polis) was studied. He regarded happiness as the highest good and described the state as an organization that ensures the protection, health, justice, and cultural rights of its citizens. During the Eastern Renaissance, the major theme of the works of prominent Central Asian thinkers such as Abu Nasr al-Farabi and Abu Ali ibn Sina (Avicenna) was the problems of the human being. In his work “The Virtuous City”, al-Farabi explored the issue of human nature and development.